Bioprospecting of indigenous myxobacteria from Iran and potential of Cystobacter as a source of anti-MDR compounds - Saadatpour, Fatemeh; Mohammadipanah, Fatemeh (Folia microbiologica, 2020)
Drug resistance is a critical issue in future clinical treatment. Methicillin-resistant Staphylococcus aureus (MRSA) is among the pathogens that need indispensable drug-discovery efforts. The myxobacteria are a unique group of bacteria that have recently been regarded for their potency to produce new drugs with high chemical diversity and unusual mode of actions. The present study was conducted to isolate and screen myxobacteria for the first time from Iran habitats and evaluate their antibacterial activity against the multidrug-resistant strain of S. aureus. Out of 62 soil and rotten plant samples, 51 myxobacteria were isolated. The isolates belonged to Myxococcus, Corallococcus, Pyxidicoccus, and Cystobacter genera based on morphology and 16S rRNA gene sequencing. Secondary metabolites of the selected strains were screened for activity on MDR strain with resistance to multiple antibiotic classes. The semi-purified fraction from Cystobacter sp. UTMC 4086 showed potent activity against MDR S. aureus with minimum inhibitory effect at 5 ≥ μg per mL compared with vancomycin (5 μg per mL) as well as no toxicity against Artemia salina. Hence, the strain Cystobacter sp. UTMC 4086 can be a valuable candidate for antibiotic discovery against MRSA and its metabolites can be subjected to further purification and analysis aimed at the identification of the effective chemical entity.
Keywords: Drug Resistance, Multiple, Bacterial; Iran; Bioprospecting; fylogeneze; mnohočetná bakteriální léková rezistence; RNA, Ribosomal, 16S; Phylogeny; antibakteriální látky; Microbial Sensitivity Tests; Myxococcales; DNA, Bacterial; DNA bakterií; Methicillin-Resistant Staphylococcus aureus; Anti-Bacterial Agents; mikrobiální testy citlivosti; RNA ribozomální 16S; bioprospekting; Írán; methicilin rezistentní Staphylococcus aureus